2009
DOI: 10.1103/physreve.79.037601
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order effects and ultrashort solitons in left-handed metamaterials

Abstract: Tsitsas, NL; Rompotis, N; Kourakis, I; Kevrekidis, PG; and Frantzeskakis, DJ, "Higher-order effects and ultrashort solitons in lefthanded metamaterials" (2009). PHYSICAL REVIEW E. 55. Retrieved from https://scholarworks.umass.edu/math_faculty_pubs/55

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 25 publications
0
46
0
5
Order By: Relevance
“…In addition, both linear and nonlinear electromagnetic properties of MMs are engineerable, thus the manipulation of electromagnetic or light waves in MMs will be more desirable. Since 2005, some dynamical models for describing ultrashort pulse propagation in MMs with a cubic nonlinear polarization and/or a nonlinear magnetization have been established [18][19][20][21][22], several intriguing and counterintuitive nonlinear phenomena associated with pulse propagation and modulation instability have been disclosed [18][19][20][21][22][23][24][25], and various soliton phenomena and physics have been demonstrated [18][19][20][21][22][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both linear and nonlinear electromagnetic properties of MMs are engineerable, thus the manipulation of electromagnetic or light waves in MMs will be more desirable. Since 2005, some dynamical models for describing ultrashort pulse propagation in MMs with a cubic nonlinear polarization and/or a nonlinear magnetization have been established [18][19][20][21][22], several intriguing and counterintuitive nonlinear phenomena associated with pulse propagation and modulation instability have been disclosed [18][19][20][21][22][23][24][25], and various soliton phenomena and physics have been demonstrated [18][19][20][21][22][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the wide study of self-focusing phenomena in Kerr nonlinear NIM has recently become a new and exciting field of research that has been the subject of intense investigations [25][26][27][28][29][30][31]. Several intriguing and counterintuitive nonlinear phenomena associated with optical collapse, optical solitons as well as modulation instability (MI) have been substantially disclosed [24][25][26][27][28][29][30][31][32][33][34][35] due to the anomalous electromagnetic properties of such materials. In particular, for MMs described by the Drude dispersive model, diffraction may be positive or negative, depending on the sign of refractive index seen by the propagating pulse in MMs [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 98%
“…Very recently, advances in the fabrication of MMs, ranging from microwave to optical frequency and from linear to nonlinear effect, have further stimulated a great deal of research including the revaluation and characterization of the classical nonlinear optical processes [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Accordingly, the wide study of self-focusing phenomena in Kerr nonlinear NIM has recently become a new and exciting field of research that has been the subject of intense investigations [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 98%
“…For example, the electromagnetic pulse propagation equation in MMs with a Kerr polarization and/or a Kerr magnetization has been reestablished [27]- [33]. In addition, several intriguing and counterintuitive nonlinear phenomena including the nonlinear interaction of ultrashort pulse with MMs [32], [33], modulation instability [34], [38], [39], and optical solitons [32], [36] have substantially been unfolded. More interestingly, for MMs described by the Drude dispersive model, our pioneer work have demonstrated that diffraction may be positive or negative, depending on the sign of refractive index seen by the propagating pulse in MMs [33], [36]- [38].…”
mentioning
confidence: 97%